(untitled) (Research, Society and Development, 2022)
Objective: To demonstrate the importance of the use of vitamins and minerals in patients with telogen effluvium, emphasizing the improvement of the patient’s pathological condition. Methodology: A search for articles on the topic was carried out in the journals available in the main health databases, Medline, Google Scholar and Pubmed, in Portuguese and English. Results: It was observed that patients with telogen effluvium, in most cases, have iron and zinc deficiency. Through some of the studies, it was possible to observe that a slightly higher percentage of participants who had the disorder had biotin deficiency, but this report does not have much evidence, and may or may not be related. A large percentage of cases with telogen effluvium are vitamin D deficient, while only a minority may experience a vitamin B12 deficiency. Patients with telogen effluvium are likely to have a decrease in ferritin levels. Regarding the deficiency of other vitamins, such as vitamin A, vitamin E, folic acid and selenium, it was not possible to detect a relationship with hair loss and their deficiency. It was evidenced, in part of the reviewed articles, that the patients had a prevalence of severe protein deficiencies, in addition to a greater deficit of amino acids. Conclusion: Although supplementation with vitamins and minerals does not present a result of great impact in the treatment of hair loss, some studies were identified that report the importance of using them, requiring further studies on the subject.